Islamic Education Management: A Study of Islamic Education Development and Supervision at a Private Islamic Elementary School in Sembalun District - Undiadi Undiadi; Yudin Citradin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study explores the implementation of Islamic education management through the development and supervision processes at SDI al-Amanah NW Kampung Karya, Sembalun District. The research aims to analyze how educational leadership and supervision practices contribute to the quality improvement of Islamic education at the primary level. Using a qualitative case study approach, data were collected through interviews, observation, and documentation involving school leaders, teachers, and stakeholders. The findings indicate that educational development is carried out through structured teacher mentoring, curriculum planning, and moral character reinforcement based on Islamic values. Supervision activities are conducted regularly, focusing on eval__uating teaching methods, student outcomes, and adherence to Islamic educational goals. Leadership plays a pivotal role in shaping a culture of professionalism and religious commitment among educators. Challenges faced include limited resources, varying teacher competencies, and community involvement. However, strong collaboration between school management and local stakeholders has helped address these issues effectively. This study concludes that effective management of Islamic education, supported by consistent development and supervision, can enhance both academic and spiritual outcomes in Islamic primary schools. The implications highlight the importance of integrated leadership and contextual supervision models to promote holistic education grounded in Islamic teachings